Development of a bivalent conjugate vaccine candidate against malaria transmission and typhoid fever. Issue 21 (17th May 2018) - An, So Jung; Scaria, Puthupparampil V.; Chen, Beth; Barnafo, Emma; Muratova, Olga; Anderson, Charles; Lambert, Lynn; Chae, Myung Hwa; Yang, Jae Seung; Duffy, Patrick E.
Abstract: Immune responses to poorly immunogenic antigens, such as polysaccharides, can be enhanced by conjugation to carriers. Our previous studies indicate that conjugation to Vi polysaccharide of Salmonella Typhi may also enhance immunogenicity of some protein carriers. We therefore explored the possibility of generating a bivalent vaccine against Plasmodium falciparum malaria and typhoid fever, which are co-endemic in many parts of the world, by conjugating Vi polysaccharide, an approved antigen in typhoid vaccine, to Pfs25, a malaria transmission blocking vaccine antigen in clinical trials. Vi-Pfs25 conjugates induced strong immune responses against both Vi and Pfs25 in mice, whereas the unconjugated antigens are poorly immunogenic. Functional assays of immune sera revealed potent transmission blocking activity mediated by anti-Pfs25 antibody and serum bactericidal activity due to anti-Vi antibody. Pfs25 conjugation to Vi modified the IgG isotype distribution of antisera, inducing a Th2 polarized immune response against Vi antigen. This conjugate may be further developed as a bivalent vaccine to concurrently target malaria and typhoid fever.